A comparison of two doses of ketamine with dexmedetomidine for fiberoptic nasotracheal intubation - Kumar, Arun (Natl J Maxillofac Surg, 2019)
BACKGROUND AND AIMS: Flexible fiber-optic intubation is considered to be the gold standard for management of difficult airway. Fiber-optic intubation does require effective sedation and blunting of airway reflexes for which various drug regimens have been utilized in the past. In a quest to find the noble drug combination, we combined ketamine and dexmedetomidine in two different doses, to evaluate the clinical efficacy and safety profile of ketamine and dexmedetomidine for fiber-optic intubation. MATERIALS AND METHODS: This prospective randomized study was conducted in 72 patients of 20–50 years’ age group of either sex with the American Society of Anesthesiologists Physical Status I and II with difficult airway. We compared two doses of ketamine 20 mg (Group I) and 40 mg (Group II) with a common dose of dexmedetomidine at 1 μg/kg body weight, given as an infusion over 10 min (a solution of 50 ml with normal saline). Sedation scores, hemodynamic variables in terms of blood pressure, heart rate (HR), and oxygen saturation were studied along with 24-h postoperative patient discomfort and recall of procedure. RESULTS: Group II patients showed less variation from their baseline values in terms of HR (ranged between 0.73% and 4.75%) and mean arterial pressure (ranged between 0% and 3.97%) in comparison to Group I HR (ranged between 0.09% and 9.81%) and mean pressures (ranged between 0.3% and 10.38%). Discomfort during procedure (P < 0.001) and recall of procedure scale (P = <0.001) were found significantly better/lower in Group II as compared to Group I. CONCLUSION: Ketamine 40 mg in comparison to 20 mg with dexmedetomidine provides better hemodynamic conditions with better tolerance and lower recall to the fiber-optic intubation.